Comparison of effectiveness of intraoperative subperiosteal versus periarticular analgesic cocktail injection for post operative analgesia in patients undergoing total knee arthroplasty - Joy, Dijo P.; E., Samson Samuel; John, P. S. (International Journal of Research in Orthopaedics, 2024)
Background: Early postoperative pain management is pivotal in patients undergoing Total knee arthroplasty. The advantage of Local infiltration analgesia is its ability to provide control of pain without interfering with motor strength of the lower extremity, thereby allowing early mobilization of patients. This study compares the effectiveness of local analgesic cocktail injection given through subperiosteal vs. periarticular routes. Methods: The study included 30 patients admitted for primary total knee arthroplasty. They were grouped into two groups based on different injection sites. Group A included patients who received subperiosteal injection and Group B included patients who received periarticular injection, under spinal anaesthesia. The difference in pain among the two groups, using VAS at 12, 24, 48, and 72 hrs postoperatively, postoperative range of movements, and Functional outcome using IKDC score at the end of 6 months were assessed and compared between the two groups. Results: The mean VAS scores at 12, 24, 48, and 72 hrs were 0.87±0.35, 1.47±0.52, 1.80±0.41, 1.07±0.46 in subperiosteal group and 2.00±0.53, 2.47±0.52, 2.80±0.56, 1.93±0.59 in periarticular group. The 6 months postoperative IKDC scores were 51.34±0.41 and 51.04±0.61 respectively. Conclusions: Subperiosteal cocktail injection can significantly reduce the postoperative pain and result in early recovery of range of movements, compared with periarticular cocktail injection in patients undergoing Total knee arthroplasty. But the long-term functional outcomes were comparable among both the groups.